2020
DOI: 10.1016/j.xinn.2020.100064
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Life Expectancy of Respiratory Diseases from Attaining Daily PM2.5 Standard in China: A Nationwide Observational Study

Abstract: This is a nationwide time-series study in 96 Chinese cities-PM 2.5 level was associated with increased risk of respiratory death-PM 2.5 level was associated with increased years of life lost of respiratory death-Daily PM 2.5 reduction might lead to longer life expectancy from respiratory death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…[4][5][6][7] Environmental factors, especially air pollution and temperature, have been widely identified to be associated with increasing risk of adverse health outcomes, such as for ischemic heart disease, stroke, diabetes, chronic obstructive pulmonary disease, and respiratory infection. [8][9][10][11] Emerging evidence indicates potential links between exposure to polluted air and COVID-19 mortality and fatality. 12,13 Recent epidemiological studies indicated that higher concentrations of pollutants were associated with worse outcome of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Environmental factors, especially air pollution and temperature, have been widely identified to be associated with increasing risk of adverse health outcomes, such as for ischemic heart disease, stroke, diabetes, chronic obstructive pulmonary disease, and respiratory infection. [8][9][10][11] Emerging evidence indicates potential links between exposure to polluted air and COVID-19 mortality and fatality. 12,13 Recent epidemiological studies indicated that higher concentrations of pollutants were associated with worse outcome of COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…There are some limitations to this study. First, like most case-crossover or time-series studies, we used province-level air pollution to represent the individual-level exposure, which is likely to cause random exposure assessment error, and thus, underestimate the PM-mortality associations [ 64 ]. However, since the same design was applied to the 2020 and 2015–2019 period, this error is not likely to affect our main findings.…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution, especially ambient particulate matter (PM), is a major environmental problem that can cause adverse health impacts. 2 , 3 Inhaled particles affect the lungs by causing chronic systemic inflammation, oxidative stress, and DNA damage to lung tissues. 4 In addition to depositing in airways, particles can also move into interstitial spaces between alveoli and circulate to other organs, which may be relevant for carcinogenic processes, although the potential mechanisms have not been fully explained.…”
Section: Introductionmentioning
confidence: 99%